Resveratrol Sensitizes Tamoxifen in Antiestrogen-Resistant Breast Cancer Cells with Epithelial-Mesenchymal Transition Features - Shi, Xiao-Peng (Molecular Diversity Preservation International (MDPI), 2013)
Tamoxifen resistance remains to be a huge obstacle in the treatment of hormone-dependent breast cancer, and this therefore highlights the dire need to explore the underlying mechanisms. The epithelial-mesenchymal transition (EMT) is a molecular process through which an epithelial cell transfers into a mesenchymal phenotype. Roles of EMT in embryo development, cancer invasion and metastasis have been extensively reported. Herein, we established tamoxifen-resistant MCF-7/TR breast cancer cells and showed that MCF-7/TR cells underwent EMT driven by enhanced endogenous TGF-β/Smad signaling. Ectopic supplement of TGF-β promoted in MCF-7 cells a mesenchymal and resistant phenotype. In parallel, we demonstrated that resveratrol was capable of synergizing with tamoxifen and triggering apoptosis in MCF-7/TR cells. Further Western blot analysis indicated that the chemosensitizing effects of resveratrol were conferred with its modulation on endogenous TGF-β production and Smad phosphorylation. In particular, 50 μM resveratrol had minor effects on MCF-7/TR cell proliferation, but could significantly attenuate endogenous TGF-β production and the Smad pathway, ultimately leading to reversion of EMT. Collectively, our study highlighted distinct roles of EMT in tamoxifen resistance and resveratrol as a potential agent to overcome acquired tamoxifen resistance. The molecular mechanism of resveratrol chemosensitizing effects is, at least in part, TGF-β/Smad-dependent.